2005
DOI: 10.1523/jneurosci.3086-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

ADrosophilaKCNQ Channel Essential for Early Embryonic Development

Abstract: The mammalian voltage-dependent KCNQ channels are responsible for distinct types of native potassium currents and are associated with several human diseases. We cloned a novel Drosophila KCNQ channel (dKCNQ) based on its sequence homology to the mammalian genes. When expressed in Chinese hamster ovary cells, dKCNQ gives rise to a slowly activating and slowly deactivating current that activates in the subthreshold voltage range. Like the M-current produced by mammalian KCNQ channels, dKCNQ current is sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 54 publications
(66 reference statements)
4
30
0
Order By: Relevance
“…8). KCNQ and Na V orthologs were present in numerous invertebrate genomes as shown previously (Plummer and Meisler, 1999;Goldin, 2002;Yu and Catterall, 2004;Wei et al, 2005;Wen et al, 2005). However, we found no examples of invertebrate KCNQ or Na V channels possessing the ankyrin-G binding motif.…”
Section: Ankyrin-g Coexpression Has Slight Effects On Kcnq2/kcnq3 Chasupporting
confidence: 76%
“…8). KCNQ and Na V orthologs were present in numerous invertebrate genomes as shown previously (Plummer and Meisler, 1999;Goldin, 2002;Yu and Catterall, 2004;Wei et al, 2005;Wen et al, 2005). However, we found no examples of invertebrate KCNQ or Na V channels possessing the ankyrin-G binding motif.…”
Section: Ankyrin-g Coexpression Has Slight Effects On Kcnq2/kcnq3 Chasupporting
confidence: 76%
“…In the tormogen, it is the apical membrane that is highly infolded, and the more likely site of the ion pump. Further, the TEP is insensitive to the Na + /K + ATPase inhibitor ouabain [87], and mutants lacking the only Drosophila KCNQ channel show no evidence of mechanosensory defects [101]. K + transport by the tormogen more likely involves the coupled activity of a proton-exporting V-ATPase and a H + /K + exchanger (as yet unidentified in Drosophila [33]), which energizes the apical surfaces of insect gut, excretory, and salivary gland cells [102].…”
Section: Ion Transport and Transduction In Es Organsmentioning
confidence: 99%
“…There is only one copy of the KCNQ gene found in Drosophila genome (Wen et al 2005) and deletion mutants of the single Drosophila KCNQ gene are viable but show a 3-fold higher than normal susceptibility to pacing-induced heart failure [see below; and (Ocorr et al 2007)]. Recent investigation of the heart rhythm of KCNQ mutants revealed that Drosophila, the only invertebrate genetic model organism with a heart (Bier and Bodmer 2004), may also be a surprisingly good model for studying the genetics of arrhythmias, as a result of both mutations and aging.…”
Section: Modulation Of the Heart Rhythmmentioning
confidence: 99%